Participation and Empowerment of Libyan Women in the Labor Market: A Study in Population Geography (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the participation and empowerment of Libyan women in the labor market from a population geography perspective by tracing changes in their participation and their demographic, educational, spatial, and sectoral characteristics. The study adopts a descriptive-analytical approach based on available statistical data from population censuses, official reports, and previous studies. It found that Libyan women’s participation in the labor force has increased significantly over time; however, it remains below the level expected in relation to their population size and educational attainment. The results also show that women’s employment is concentrated mainly in government and service sectors, especially education, health, and public administration, while their presence remains limited in productive sectors and the private sector. The study revealed a gap between the relatively high educational level of Libyan women and their actual participation in the labor market, as well as clear spatial disparities between major coastal cities and rural, inland, and southern areas. It also concluded that barriers to women’s participation are intertwined across demographic, spatial, social, economic, and security dimensions, which calls for multi-dimensional policies to enhance women’s economic empowerment.
Keywords: population geography, Libyan women, labor market, economic empowerment, workforce, spatial inequality